Record high extraction efficiency of free electron laser oscillator. (1st October 2020) - Zen, Heishun; Ohgaki, Hideaki; Hajima, Ryoichi
Abstract: The highest extraction efficiency (9.4%) of a free electron laser (FEL) oscillator has been achieved at the midinfrared FEL facility of Kyoto University. Because of the interaction between the electron beam and FEL electromagnetic field, a maximum electron energy decrease of 16% was observed. The measured energy decrease was consistent with the measured FEL spectrum. An FEL micropulse energy of ∼100 μ J with the expected few-cycle pulse duration at a wavelength of 11 μ m was observed. This result is an important milestone for the high-extraction-efficiency FEL oscillator and will contribute to the strong-field physics of atoms and molecules.